INTEGRATING THE CONCEPT OE SUSTAINABLE DEVELOPMENT INTO NATIONAL POLICIES: THE ROLE OF INDONESIAN GOVERNMENT IN TOURISM DEVELOPMENT - Micke Anggraini, Luh (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2007)
Tourism in Indonesia has rapidly developed and has supported the economic development of the country over three decades. Along with the issues of global sustainability, most governments in the world, including Indonesia, have committed to developing tourism in a sustainable manner. The national tourism policy thus becomes an important tool to control the development, where the natural and cultural resources are intensively utilized to support tourism. As a focal part in policy making, the national government has a significant role to ensure the attainment of sustainable tourism. However, the integration of the concept of sustainable development in the national tourism policy has been moderated when the economy of Indonesia particularly in the tourism industry is currently facing depression and has not to get back to the level as achieved in the past decade.